R. M. Clarken, Charter and Ordinances of the City of Sacramento 173 (1896) - (:unkn) unknown (My University, 1876)
Ordinance no. 84: Prohibiting the Carrying of Concealed Deadly Weapons. Passed April 24, 1876: Prohibited any person from wearing or carrying concealed any pistol, dirk, or other dangerous or deadly weapon. Violators fined not exceeding five hundred dollars, or imprisonment not exceeding ten days, or both.
Keywords: CARRY - CONCEALED